Do Protestant Missionaries Undermine Political Authority? Evidence From Peru - Anselm Rink (Comparative Political Studies, 2018)
The relation between religious organizations and political authority is notoriously tense. Max Weber argued that this is because both compete over the same resource: human commitment. This article revisits Weber's hypothesis. Specifically, we explore two psychological mechanisms through which Protestant missionaries affect political authority: obedience and persuadability. Exploiting exogenous variation in missionary activity in Peru, we demonstrate that missionaries make converts more obedient, which we attribute to a theological and a social mechanism. Yet, we also find that missionaries make converts less susceptible to persuasion by political authorities because they shift attention from secular topics to questions of theological importance, and endorse a skeptical stance toward the government. Exploiting variation in treatment intensity, we argue that the degree to which political authority is affected depends on a given mission's theological strictness. We arrive at these findings by combining experimental outcomes and process-tracing evidence using Bayesian integration.
Additional information: Dieser Beitrag ist mit Zustimmung des Rechteinhabers aufgrund einer (DFG-geförderten) Allianz- bzw. Nationallizenz frei zugänglich / This publication is with permission of the rights owner freely accessible due to an Alliance licence and a national licence (funded by the DFG, German Research Foundation) respectively.; http://doi.org/10.7910/DVN/B075NQ
Keywords: 320; religion and politics; quantitative methods; Latin American politics